EGYPT IN THE EYES OF THE FIRST FRENCH PHOTOGRAPHERS - Salama, Dr. Yousra Mohamed (Journal of Historical Studies, 2020)
The French invasion of Egypt sparked a national passion for all of Egypt's ancient Pharaonic history. Napoleon not only came to invade Egypt, but brought with him more than 150 scientists, cartographers, artists, naturalists and even musicians and painters; Observing the details of ancient sites and existing customs, the result was the huge work "Description of Egypt", published between 1809 and 1829, in twenty volumes, containing about 900 inscriptions. The French scientist François Arago (1786 - 1853) regretted that photography had not been invented yet. As he announced in Paris on January 7, 1839, he invented the photographic design designed by Louis-Jacques-Mand Daguerre to copy millions of hieroglyphs covering the exterior of the great monuments at Thebes, Memphis, Karnak, etc., you'll need decades of hordes of painters, but with the invention of Daguerre, one person is enough to do so. In announcing the invention of photography, Arago pledged to harness this invention in the service of science - and was intended to replace the cartoons of the book Description of Egypt; The attention of photographers, they showed the beauty of the region, as well as recording the landmarks of this civilization. These early photographers also presented a series of unique images of Egypt, thereby deepening the French public's sense of the greatness of the Egyptian civilization, and the world in general, with the legacy they documented. Thousands of years ago, they have stimulated those who will come after them to see all these tourist places, and the interest in the region, which has already increased with the development in the process of photography, which contributed to the increase of desire and see those places and take pictures of them.